Impact of OHS Practices on Employee Engagement: An Applied Study in Five-Star Hotels in the City of Sana'a - السفياني، عبدالرحمن محمد (جامعة تعز فرع التربة - دائرة الدراسات العليا والبحث العلمي, 2021)
The aim of this study is to investigate the impact of occupational health and safety practices on employee engagement in the five-star hotels in the city of Sana’a. The Study depended on the descriptive approach and used the questionnaire tool that was designed according to the five-Likert scale. The data distributed and collected from 195 employees working in in the five-star hotels in the Yemeni city of Sana’a. The results indicate that the reality of implementing occupational health and safety practices in the five star hotels is medium, and the level of employee engagement is high. Also, the results show that there is a statistically significant impact of occupational health and safety practices (simultaneously) on employee engagement. Besides, the two variables (top management commitment and OHS training) among the other variables of OHS Practices have been a significant impact on the employee engagement. Further, the results show that an estimated 30.4% of the variance in overall employee engagement can be accounted for by the occupational health and safety practices. Finally, suggestions may be made to the managements of five-star hotels in the city of Sana’a to pay more attention to occupational health and safety practices to maintain and protect their employees from dangers and deases that are occurring in the work place because of its importance in enhancing the employee engagement.
الهدف من هذه الدراسة هو التحقيق من أثر ممارسات الصحة والسلامة المهنية على ارتباط الموظفين في الفنادق فئة الخمس نجوم في مدينة صنعاء. اعتمدت الدراسة على المنهج الوصفي واستخدمت أداة الاستبيان التي تم تصميمها وفقا لمقياس ليكرت الخماسي. تم توزيع وجمع البيانات من 195 موظفا ممن يعملون في فنادق الخمس نجوم في مدينة صنعاء اليمنية. وتشير النتائج إلى أن واقع تطبيق ممارسات الصحة والسلامة المهنية في فنادق الخمس نجوم متوسط، ومستوى ارتباط الموظفين مرتفع. تظهر النتائج أيضا أن هناك تأثيرا ذو دلالة إحصائية لممارسات الصحة والسلامة المهنية (في وقت واحد) على ارتباط الموظفين. إلى جانب ذلك، فإن المتغيرين (التزام الإدارة العليا وتدريب الصحة والسلامة المهنية) من بين المتغيرات الأخرى لممارسات الصحة والسلامة المهنية لهما تأثير كبير على ارتباط الموظفين. علاوة على ذلك، تظهر النتائج أن ما يقدر بـ 30.4% من التباين الكلي لارتباط الموظفين يمكن تفسيره من خلال ممارسات الصحة والسلامة المهنية. أخيرا، يمكن تقديم مقترحات إلى إدارات فنادق الخمس نجوم في مدينة صنعاء بإيلاء مزيدا من الاهتمام بممارسات الصحة والسلامة المهنية للحفاظ على موظفيها وحمايتهم من الأخطار والأمراض التي تحدث في مكان العمل بسبب أهميتها في تعزيز ارتباط الموظفين.
Keywords: السلامة المهنية -- الرعاية الصحية -- الموارد البشرية -- الفنادق السياحية -- السلوك التنظيمي